The impact of Bacillus subtilis DSM32315 and L-Threonine supplementation on the amino acid composition of eggs and early post-hatch performance of ducklings - Azzam, Mahmoud Mostafa; Chen, Wei; Xia, Weiguang; Wang, Shuang; Zhang, Yanan; El-Senousey, HebatAllah Kasem; Zheng, Chuntian (Frontiers in Veterinary Science, 2023)
Poultry requires Threonine, an essential amino acid, and its metabolites for proper metabolic function. Threonine is crucial in the biosynthesis of mucin, which is essential for intestinal health and nutrient absorption. Bacillus Subtilis (B. subtilis) is a potential substitute for antibiotic growth promoters in the poultry industry. The current study was designed to evaluate the simultaneous effect of L-Threonine (Thr) and B. subtilis DSM32315 supplementation on laying duck breeders in order to maximize performance. A total number of 648 female 23-week-old Longyan duck breeders were assigned to a 3 × 2 factorial design with six replicates of 18 birds per replicate. L-Thr was added to the control diet at concentrations of 0, 0.7, and 1.4 g/kg, equating to 3.9, 4.6, and 5.3 g Thr/kg, with or without B. Subtilis strain DSM 32315 (0.0 and 0.5 g/kg). Increasing Thr concentrations improved ducklings' egg production and hatchling weight (P<0.05). In addition, L-Thr supplementation resulted in a tendency for decreased feed conversion ratio without affecting egg quality. There was no significant effect (P>0.05) of the dietary Thr levels on egg yolk and albumen amino acid concentrations. In contrast, the addition of B. Subtilis decreased the concentrations of amino acids, excluding proline, in the egg white (albumen) and the egg yolk (P<0.05). Furthermore, the supplementation of B. Subtilis decreased (P<0 .001) the hatching weight of ducklings. The addition of B. Subtilis without L-Thr decreased (P< 0.05) the hatchability of fertile eggs and the hatching weight of ducklings compared to those of ducks fed dietary L-Thr along with B. Subtilis (P<0.001). The present findings concluded that combining L-Thr at 0.7 g/kg with B. subtilis DSM 32315 at 0.5 g/kg could increase eggshell quality, hatchability, and hatching weight. Additionally, adding L-Thr at 0.7 g/kg could improve egg production in laying duck breeders. However, more research is needed to determine the effective dosages of B. subtilis DSM 32315 when combined with limiting amino acids in the diets of duck breeders. The findings of this study will encourage the use of antibiotic-free feed additive interventions.